O grito da resistência: o jornal posição e a cobertura da abertura política no Espírito Santo (1976 a 1981) - Brumana, Luiz Fernando da Silva (2016)
During the 20 years of the Military Dictatorship, oppositional groups have articulated to denounce the regime's atrocities. In Espírito Santo, an exponent of struggle was the newspaper called Posição, created in the second half of the 1970s, when subjects like Amnesty and the return of democracy gained strength among people. It is the way actions for Amnesty and the end of the dictatorial process were described by the ephemeral Capixaba publication that will be discussed in this dissertation. Looking for investigate the guidelines, the reason for covering Amnesty campaigns so well and how the reports contributed to the political prisoners - especially with the former student of the Federal University of Espírito Santo Perly Cipriano - an extensive research program was promoted from the documentary analysis of more than sixty editions of the Posição and the book "A Esquerda Armada", written by members of the newspaper. Also, interviews were given by journalists, newspaper contributors and officials of the time to contextualize that period. From where we can see the historical importance of the alternative publication Posição for the trajectory of the Espírito Santo journalism and the history of Espírito Santo itself